2014
DOI: 10.1155/2014/257807
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Human Papillomavirus Vaccine: A Survey among Master of Business Administration Students in KwaZulu-Natal, South Africa

Abstract: Cervical cancer is a preventable public health problem. The two new human papillomavirus (HPV) vaccines are available but not accessible to everyone in South Africa, as they are very expensive. This study aimed to investigate educated peoples acceptability regarding HPV vaccination. This was a cross-sectional survey conducted among 146 master of business administration students by self-administered, anonymous questionnaire. The majority (74%) of the participants ever heard of cervical cancer, but only 26.2% he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…A South African study conducted among educated people such as master of business administration (MBA) students reported that most participants were aware of cervical cancer, but only about a quarter had heard about HPV. 13 A Chinese study conducted among employed women and undergraduate students found that 28% of employed women and 12% of university students had heard of HPV, while only 21% of employed women and 7.2% of students knew that HPV is related to cervical cancer. 14 The Indian study found that only a third of the educated parents of adolescents were aware of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A South African study conducted among educated people such as master of business administration (MBA) students reported that most participants were aware of cervical cancer, but only about a quarter had heard about HPV. 13 A Chinese study conducted among employed women and undergraduate students found that 28% of employed women and 12% of university students had heard of HPV, while only 21% of employed women and 7.2% of students knew that HPV is related to cervical cancer. 14 The Indian study found that only a third of the educated parents of adolescents were aware of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is quite low, as the previous study conducted among educated people in South Africa reported 90% of the participants vaccinating their children using the regular vaccines. 13 It is expected that the current group of people are educated and aware of the benefits of the vaccines. The low rate of vaccination could be a result of the influence of the anti-vaccination lobby in South Africa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a wide global variation on cervical cancer awareness and HPV vaccination acceptability is reported in 604 several reports [133][134][135]. In our study participants, HPV vaccination was the least improved category even after 605 education intervention.…”
mentioning
confidence: 71%